Penyesuaian Tarif PBJT atas Jasa Hiburan Tertentu Dalam Menunjang Daya Saing Jakarta Sebagai Global City (Studi Kasus UU No 2 Tahun 2024 Tentang Provinsi Daerah Khusus Jakarta) - Kurniawan, Hendra; Abadi, Fiter (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the adjustment of the Tax on Certain Goods and Services (PBJT) rates in the entertainment sector in Jakarta following the enactment of Law Number 2 of 2024 concerning the Jakarta Special Region, as well as the economic impact of this new policy on the entertainment industry in the region. The relocation of Indonesia’s capital from Jakarta to the Nusantara Capital City (IKN) in East Kalimantan, through Law Number 3 of 2022, forces Jakarta to adapt to new challenges to maintain its position as the national economic center. Currently, the entertainment sector in Jakarta still significantly contributes to Regional Original Revenue (PAD) through PBJT revenue, regulated by Law Number 1 of 2022 on Financial Relations between the Central and Regional Governments (UU HKPD) with a tax rate range of 40% - 75% and Law No. 2 of 2024, with a tax rate range of 25% - 75% for certain entertainment services. This research employs a qualitative approach with a literature review method. Data are obtained through document analysis and interviews with stakeholders, including entertainment industry players, related associations, and government representatives. This study also evaluates a comparison of entertainment tax rate policies in Southeast Asian countries, such as Thailand, Malaysia, Vietnam, and the Philippines, to understand how the tax policy implemented in Jakarta may affect the city’s competitiveness as a global city. Several entertainment industry players have filed judicial reviews in the Constitutional Court, arguing that high entertainment tax rates could harm their constitutional rights and reduce Jakarta’s competitiveness in the global city index. The findings of this study are expected to provide deeper insights into the impact of tax policy changes on the entertainment sector in Jakarta and to offer recommendations for the government in establishing tax policies that support economic sustainability and Jakarta's competitiveness as a global city.
Keywords: Adjustment of PBJT Rates on Certain Art and Entertainment Services; Jakarta Special Region; Global City Competitiveness